Neuromuscular transmission studies in human chronic Chagas' disease - Marcela Garcia Erro; O. Genovese; J. Correale; R. E. P. Sica (Arquivos de Neuro-Psiquiatria)
An electrophysiological investigation of the state of the neuromuscular transmission (nmt) was carried out in 58 patients with the diagnosis of chronic Chagas' disease. On repetitive supramaximal nerve stimulation it was found that some patients did not show abnormalities, others had decremental muscle responses, others developed enhancement of the muscle evoked potential amplitudes, while some other patients combined both types of pathological responses. The findings suggest that some patients with chronic Chagas' disease develop impairement of nmt, though data obtained in this study do not give information about neither the type of impairement nor the localization (pre or postsynaptic, or both) of the damage.